2016
DOI: 10.1016/j.krcp.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of patients with IgA nephropathy in Japan

Abstract: Chronic kidney disease (CKD) is a worldwide public health problem that affects millions of people from all racial and ethnic groups. Although CKD is not one specific disease, it is a comprehensive syndrome that includes IgA nephropathy. As reported by the Japanese Society of Nephrology, 13.0 million people have CKD. In Japan, major causes of end-stage kidney disease are type 2 diabetic nephropathy, chronic glomerulonephritis, especially IgA nephropathy, hypertensive nephrosclerosis, and polycystic kidney disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 18 publications
1
34
0
2
Order By: Relevance
“…IgAN is the most prevalent primary glomerulonephritis and that it accounts for 28.3% of the glomerular disease confirmed by biopsy 4 . Similar results have been shown in Japan 5 and in China 6 .…”
supporting
confidence: 89%
“…IgAN is the most prevalent primary glomerulonephritis and that it accounts for 28.3% of the glomerular disease confirmed by biopsy 4 . Similar results have been shown in Japan 5 and in China 6 .…”
supporting
confidence: 89%
“…Therapeutic regimens, including information about treatment with renin-angiotensin system inhibitors and oral steroids, were assessed and TSP implementation was also analyzed in the patients with IgAN. Indications and the regimen for TSP are detailed elsewhere [ 26 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…These studies identified excess Gd-IgA1 in both serum and glomerular immune deposits of patients with IgAN [ 19 , 20 , 25 ]. Furthermore, the recently proposed multi-hit theory of IgAN states that overproduced Gd-IgA1 and autoantibodies against Gd-IgA1 subsequently form circulating immune complexes (IC), resulting in glomerular mesangial deposits followed by accelerated nephritis [ 19 , 26 ]. Thus, Gd-IgA1 is vital to the pathogenesis of IgAN, and Gd-IgA1 (s-Gd-IgA1) or mesangial Gd-IgA1 (m-Gd-IgA1) could serve as candidate disease-specific biomarkers that reflect severity and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, implementation of steroid pulse therapy combined with tonsillectomy (TSP) after RB was also analyzed. Indications for and the regimen for TSP in IgAN are detailed elsewhere [24,33,34].…”
Section: Plos Onementioning
confidence: 99%
“…These studies identified excess Gd-IgA1 in both serum and glomerular immune deposits in patients with IgAN [20][21][22][23]. Furthermore, the recently proposed multi-hit theory of IgAN states that overproduced Gd-IgA1 and autoantibodies against Gd-IgA1 subsequently form circulating IC, resulting in glomerular mesangial deposits followed by accelerated nephritis [20,24]. Thus, Gd-IgA1 is vital to the pathogenesis of IgAN.…”
Section: Introductionmentioning
confidence: 99%